Penal populism, sentencing councils and sentencing policy - Freiberg, Arie; Gelb, Karen (Sydney : Hawkins Press, 2008)
'With particular emphasis on the emerging role of sentencing commissions, advisory councils or panels in a number of English speaking countries, this book brings together the theoretical perspectives on the role of the public in the development of sentencing policy.'--Provided by publisher
Penal populism, sentencing councils and sentencing policy / Arie Freiberg and Karen Gelb -- Sentencing policy and practice : the evolving role of public opinion / Julian V. Roberts -- Penal scandal in New Zealand / John Pratt -- Dealing the public in : challenges for a transparent and accountable sentencing policy / David Indermaur -- Myths and misconceptions : public opinion versus public judgment about sentencing / Karen Gelb -- The Minnesota sentencing guidelines / Richard S. Frase -- The United States Sentencing Commission / Nancy Gertner -- English sentencing guidelines in their public and political context / Andrew Ashworth -- The New South Wales Sentencing Council / Alan Abadee -- The Sentencing Commission for Scotland / Neil Hutton -- The Victorian Sentencing Advisory Council : incorporating community views into the sentencing process / Arie Freiberg -- A perspective on the work of the Victorian Sentencing Advisory Council and its potential to promote respect and equality for women / Therese McCarthy -- Sentencing reform in New Zealand : a proposal to establish a sentencing council / Warren Young -- A sentencing council in South Africa / Stephan Terblanche -- A federal sentencing council for Australia / Australian Law Reform Commission -- Institutional mechanisms for incorporating the public / Neil Hutton -- Does it matter? Reflections of the effectiveness of institutionalised public participation in the development of sentencing policy / Rob Allen and Mike Hough
Includes bibliographical references and index
Keywords: Sentences (Criminal procedure) -- Public opinion; Sentences (Criminal procedure) -- Citizen participation; Sentences (Criminal procedure)